Islamic Inheritance Law Reform in Indonesia from the Perspective of Islamic Legal Politics: Strategies and Implications - Firmansyah, Heri; Nas, Zulkifli (Hukum Keluarga Islam IAIN LANGSA, 2024)
This research aims to analyze the reform of Islamic inheritance law in Indonesia, with a particular focus on government policies supporting this reform. The study examines legal doctrines in the Compilation of Islamic Law, jurisprudence, Supreme Court guidance letters for religious courts, and fatwas from the Indonesian Ulema Council. Employing a historical and Islamic legal political (fiqh siyasah) approach, it explores the background and dynamics of these reforms. The reform process involves updating legal concepts, norms, and techniques, driven primarily by the executive and judiciary, while legislative bodies are constrained by their inability to pass laws. Non-governmental institutions, particularly the Indonesian Ulema Council, also play a pivotal role. Scientifically grounded methods, such as ijtihad intiqa'i tarjihi and ibda'i insha'i, serve as the foundation for these reforms. The government’s strategies within the Islamic legal-political framework (fiqh siyasah) are (1) developing Islamic inheritance law in line with societal practices, (2) codifying it into legislative products, (3) compiling it into unified legal texts, (4) enacting legal products such as presidential instructions, fatwas, and jurisprudence, (5) involving scholars, officials, and judges in shaping reforms, (6) creating regulations for non-litigious inheritance distribution based on Islamic law, and (7) engaging the community in inheritance practices. This research’s novelty lies in its comprehensive analysis of both governmental and non-governmental roles in reforming Islamic inheritance law through integrative legal-political strategies. Additionally, it highlights the innovative application of ijtihad intiqa'i tarjihi and ibda'i insha'i, contributing to the modernization and contextualization of Islamic inheritance law in Indonesia. The contribution of this research is its exploration of the interplay between legal reform and societal practices, providing a new understanding of the mechanisms that shape Islamic law in contemporary Indonesia. Furthermore, it offers valuable insights into the role of both religious scholars and government authorities in the legal reform process, offering a model for integrating Islamic law with modern legal systems.